Blog Folio in Blended Learning: a Development of Studentsâ Information Processing Skills in Digital Age - Rahmi, Ulfia; Darmawan, Deni (AT-TALIM, 2018)
Paradigm shift in educational context support to instructional innovation, such as online learning, blended learning, and mobile learning. Researcher implemented the blended learning by using blog as portfolios for students. The purpose in this research was to identify the effects of using a blog in blended learning to improve collage studentâs information processing skill in virtual environment. The facilitation given to college students in order to familiar with through search, collect, manages, and communicates information in digital age. Research subject is collage students in Development of Innovation Instructional Model course on period January-June 2017 at Educational Technology in Universitas Negeri Padang. This research used three instruments, consist of 1) the rubrics for identify information processing skill, 2) questionnaire for using blog folio, and 3) interview guided about advantages, challenges and obstacles to use a blog in blended learning. The result show that using blog folio can help collage students to improved information processing skills because they understood and tried the steps of that skill. Furthermore, they admitted by using blog folio can increased motivation, participation and give advantages.